2008
DOI: 10.1038/bmt.2008.343
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with autologous stem cell transplantation for multiple myeloma: what predicts the outcome? Experience from a developing country

Abstract: We analyzed the results of 108 patients (78 males and 30 females) with multiple myeloma who underwent autologous stem cell transplantation (ASCT). The median age of patients was 52 years (range, 26-68 years). High-dose melphalan (200 mg/m 2 ) was used for conditioning. In all, 66 (61%) patients had evidence of chemo-sensitive disease before transplant. After ASCT 79.6% of patients responded: complete response 36%, very good partial response 29.6%, and partial response 13.9%. Complete response rate was higher f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Our centre is performing autologous HSCT for multiple myeloma since year 2007 and our analysis of these 31 patients shows results comparable to international and other Indian centres results (Table 5) [12][13][14][15][16]. One Indian study described by Lalit Kumar et al showed median EFS & OS of 42 months & 71 months respectively.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our centre is performing autologous HSCT for multiple myeloma since year 2007 and our analysis of these 31 patients shows results comparable to international and other Indian centres results (Table 5) [12][13][14][15][16]. One Indian study described by Lalit Kumar et al showed median EFS & OS of 42 months & 71 months respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Complications profile related to transplant is also comparable to other institutes data with exception of very low incidence of oral mucositis. Other studies have shown average 50 to 70% overall incidence of oral mucositis with 15 to 25% having severe form, however our data shows that only 3 (9.6%) patients had developed grade 2+3 oral mucositis [12][13][14][15][16]. Most important intervention which has helped in preventing oral mucositis in our patients is strictly following continuous ice sucking during Melphalan infusion, a proven intervention [11].…”
Section: Discussionmentioning
confidence: 61%
“…There is limited information regarding the efficacy, adverse effects or the long term complications of the induction regimens. 15 Therefore we sought to evaluate the efficacy and safety of the bortezomib plus dexamethasone as induction treatment followed by ASCT in newly diagnosed patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…Markov state transition probabilities of moving from one health state to another were computed using date on progression free survival, while the probability to die due to multiple myeloma was computed using the overall survival [18,19].…”
Section: Clinical and Epidemiological Parametersmentioning
confidence: 99%